Electromyographic activity using elastic resistance and nautilus machine exercises - Aboodarda, S.J.; Muhamed, A.M.C.; Ibrahim, F.; Hamid, M.S.B.A. (2009)
The purpose of this study, therefore, was to quantify and compare Integrated Electromyography (I-EMG) within perfuming 8-RM seated knee extension in contribution of Elastic Resistance and Nautilus Machine exercises. All data were collected within one testing session. Subjects completed 8RM seated knee extension by three modalities of resistance exercises comprised of Nautilus Machine (NM), elastic tubing with original elongation (E0) and elastic tubing with 30 decrement of original elongation (E30). Electromyographic muscle activation and range of motion were collected and synchronized from Vastus Lateralis (VL). Results: manipulating the resting length of elastic resistance resulted in significantly higher I-EMG for E30 in compare with E0 (25 increasing muscle activation); however, no significant difference observed between E30 and NM (P = 0.443). Based on these results, it seems that shortened form of elastic exercise (E30) and NM exercises offer equivalent muscle activation. Thus, they could be used interchangeably for lower body strength development.